Treating critically ill patients with probiotics: Beneficial or dangerous? - Jacobi, Christoph A (BioMed Central, 2011)
Probiotic bacteria are live microorganisms which confer to health benefits of the host. They help to maintain the integrity of the intestinal barrier function by modulating the mucosal and systemic immune response of the host. These bacteria have proven their beneficial effect in several conditions of ulcerative colitis. More recently probiotics/synbiotics have been included in the treatment of critically ill patients. However to date it remains uncertain whether probiotics/synbiotics are beneficial or even dangerous to the clinical outcome of this patient group. This article reviews the current evidence of the use of bacteria in critically ill patients in intensive care settings.